Dressing and securement for central venous access devices (CVADs): A Cochrane systematic review. (July 2016) - Ullman, Amanda J.; Cooke, Marie L.; Mitchell, Marion; Lin, Frances; New, Karen; Long, Debbie A.; Mihala, Gabor; Rickard, Claire M.
Abstract: Objectives: To compare the available dressing and securement devices for central venous access devices (CVADs). Design: Systematic review of randomised controlled trials. Data sources: Cochrane Wounds Group Specialised Register, the Cochrane Central Register of Controlled Trials, the Database of Abstracts of Reviews and of Effects, NHS Economic Evaluation Database, Ovid MEDLINE, CINAHL, EMBASE, clinical trial registries and reference lists of identified trials. Review methods: Studies evaluated the effects of dressing and securement devices for CVADs. All types of CVADs were included. Outcome measures were CVAD-related bloodstream infection, CVAD tip colonisation, entry and exit site infection, skin colonisation, skin irritation, failed CVAD securement, dressing condition and mortality. We used standard methodological approaches as expected by The Cochrane Collaboration. Results: We included 22 studies involving 7436 participants comparing nine different types of securement device or dressing. All included studies were at unclear or high risk of performance bias due to the different appearances of the dressings and securement devices. It is unclear whether there is a difference in the rate of CVAD-related bloodstream infection between securement with gauze and tape and standard polyurethane (RR 0.64, 95% CI 0.26 to 1.63, low quality evidence), or between chlorhexidine gluconate-impregnated dressings and standard polyurethane (RR 0.65, 95% CI 0.40 to 1.05, moderate quality evidence). There is high quality evidence that medication-impregnated dressings reduce the incidence of CVAD-related bloodstream infection relative to all other dressing types (RR 0.60, 95% CI 0.39 to 0.93). There is moderate quality evidence that chlorhexidine gluconate-impregnated dressings reduce the frequency of CVAD-related bloodstream infection per 1000 patient days compared with standard polyurethane dressings (RR 0.51, 95% CI 0.33 to 0.78). There is moderate quality evidence that catheter tip colonisation is reduced with chlorhexidine gluconate-impregnated dressings compared with standard polyurethane dressings (RR 0.58, 95% CI 0.47 to 0.73), but the relative effects of gauze and tape and standard polyurethane are unclear (RR 0.95, 95% CI 0.51 to 1.77, very low quality evidence). Conclusions: Medication-impregnated dressing products reduce the incidence of CVAD-related bloodstream infection relative to all other dressing types. There is some evidence that chlorhexidine gluconate-impregnated dressings, relative to standard polyurethane dressings, reduce CVAD-related bloodstream infection for the outcomes of frequency of infection per 1000 patient days, risk of catheter tip colonisation and possibly risk of CVAD-related bloodstream infection. Most studies were conducted in intensive care unit settings. More, high quality research is needed regarding the relative effects of dressing and securement products for CVADs.